Lithium-ion-transfer kinetics of single LiMn2O4 particles - Zampardi, G; Batchelor-McAuley, C; Kätelhön, E; Compton, R (Wiley, 2016)
A stochastic investigation of lithium deinsertion from individual 200-nm-sized particles of LiMn2 O4 reveals the rate-determining step at high overpotentials to be the transfer of the cation across the particle-electrolyte interface. Measurement of the (electro)chemical behavior of the spinel is undertaken without forming a conductive composite electrode. The kinetics of the interfacial ion transfer defines a theoretical upper limit for the discharge rates of batteries using LiMn2 O4 in an aqueous environment.